2014
DOI: 10.1210/jc.2014-1736
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Parathyroid Hormone Is Associated with Vascular Dementia and Cerebral Hyperintensities in Two Community-Based Cohorts

Abstract: In two community-based samples, PTH predicted clinically diagnosed vascular dementia as well as neuroimaging indices of cerebral small vessel disease. Our data suggest a role for PTH in the development of vascular dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 35 publications
1
24
1
Order By: Relevance
“…In contrast to Hagström et al 17 , we did not observe any association of PTH with subclinical cerebrovascular disease after adjustment for CVD risk factors and 25(OH)D levels. Prior work in the ARIC Brain MRI study has found that cumulative systolic blood pressure was a strong predictor of WMH progression over follow-up, 19 and since PTH is associated with incident hypertension, 3 we had hypothesized that hypertension might be a mediator in the biologic pathway between elevated PTH levels and cerebrovascular disease.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to Hagström et al 17 , we did not observe any association of PTH with subclinical cerebrovascular disease after adjustment for CVD risk factors and 25(OH)D levels. Prior work in the ARIC Brain MRI study has found that cumulative systolic blood pressure was a strong predictor of WMH progression over follow-up, 19 and since PTH is associated with incident hypertension, 3 we had hypothesized that hypertension might be a mediator in the biologic pathway between elevated PTH levels and cerebrovascular disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Although our study sample was much larger than the one in the previously published paper by Hagström et al 17 (n=1703 in our sample vs n=406 in their study), our study may still be underpowered for prospective analyses as mentioned above. Because the sample was relatively young at the time of both brain MRIs, most participants had relatively minimal WMH, with relatively low rates of infarcts at both MRIs.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations